The Exodus-conquest narrative the composition of the non-priestly narratives in Exodus-Joshua - Germany, Stephen 1985-; Mohr Siebeck GmbH & Co. KG; Emory University (Tübingen Mohr Siebeck, 2017)
"Cover" -- "Preface" -- "Table of Contents" -- "Chapter 1: Introduction" -- "1. Contextualization of the Problem" -- "2. Methodology" -- "Chapter 2: Out of Egypt (Exod 1â12)" -- "1. Pharaohâs Oppression of the Israelites (Exod 1)" -- "1.1. Literary-critical analysis" -- "1.2. Macrocontextual analysis" -- "1.3. Synthesis" -- "2. Mosesâ Birth and Flight from Egypt (Exod 2:1-15abÎ±)" -- "2.1. Literary-critical analysis" -- "2.2. Macrocontextual analysis" -- "2.3. Synthesis" -- "3. Moses in Midian (Exod 2:15bÎ²â4:31)" -- "3.1. Literary-critical analysis" -- "3.2. Macrocontextual analysis" -- "3.3. Synthesis" -- "4. The First Encounter with Pharaoh (Exod 5:1â6:1)" -- "4.1. Literary-critical analysis" -- "4.2. Macrocontextual analysis" -- "4.3. Synthesis" -- "5. A Second Commissioning of Moses (Exod 6:2â7:7)" -- "5.1. Literary-critical analysis" -- "5.2. Macrocontextual analysis" -- "5.3. Synthesis" -- "6. The Plagues and the Departure from Egypt (Exod 7:8â12:51)" -- "6.1. Literary-critical analysis" -- "6.2. Macrocontextual analysis" -- "6.3. Synthesis" -- "7. Result " -- "Chapter 3: Into the Wilderness (Exod 13â18)" -- "1. The Itinerary Notices in Exodus and Numbers" -- "2. The Miracle at the Sea (Exod 13:17â14:31)" -- "2.1. Literary-critical analysis" -- "2.2. Macrocontextual analysis" -- "2.3. Synthesis" -- "3. The Song at the Sea and the Song of Miriam (Exod 15:1-21)" -- "3.1. Literary-critical analysis" -- "3.2. Macrocontextual analysis" -- "3.3. Synthesis" -- "4. Marah and Elim (Exod 15:22-27)" -- "4.1. Literary-critical analysis" -- "4.2. Macrocontextual analysis" -- "4.3. Synthesis" -- "5. Quails and Manna (Exod 16)" -- "5.1. Literary-critical analysis" -- "5.2. Macrocontextual analysis" -- "5.3. Synthesis" -- "6. Water from a Rock (Exod 17:1Î²b-7)" -- "6.1. Literary-critical analysis" -- "6.2. Macrocontextual analysis
"6.3. Synthesis" -- "7. The War with Amalek (Exod 17:8-16)" -- "7.1. Literary-critical analysis" -- "7.2. Macrocontextual analysis" -- "7.3. Synthesis" -- "8. Jethro (Exod 18)" -- "8.1. Literary-critical analysis" -- "8.2. Macrocontextual analysis" -- "8.3. Synthesis" -- "9. Result" -- "Chapter 4: The Revelation of the Law at Sinai (Exod 19â24 // Deut 5:1â6:3)" -- "1. Exod 19â24" -- "1.1. Literary-critical analysis" -- "1.2. Macrocontextual analysis" -- "1.2.1. The theophany texts" -- "1.2.2. The narratives relating to the law " -- "1.2.3. The theophany without the law (Scenario 1)" -- "1.2.4. The law without the theophany (Scenario 2)" -- "1.2.5. Law and theophany together (Scenario 3)" -- "1.3. Synthesis" -- "2. Deut 5:1â6:3" -- "2.1. Literary-critical analysis" -- "2.2. Synthesis" -- "3. Comparison of Exod 19â24 and Deut 5:1â6:3" -- "4. Result" -- "Chapter 5: The Golden Calf and Its Aftermath (Exod 32â34 // Deut 9:7â10:11)" -- "1. Exod 32â34" -- "1.1. Literary-critical analysis" -- "1.2. Macrocontextual analysis" -- "1.3. Synthesis" -- "2. Deut 9:7â10:11" -- "2.1. Literary-critical analysis" -- "2.2. Synthesis" -- "3. Comparison of Exod 32â34 and Deut 9:7â10:11" -- "4. Result" -- "Chapter 6: From Sinai to Kadesh (Num 10â19)" -- "1. The Peopleâs Departure (Num 10:29-36)" -- "1.1. Literary-critical analysis" -- "1.2. Macrocontextual analysis" -- "1.3. Synthesis" -- "2. Further Complaints in the Wilderness (Num 11)" -- "2.1. Literary-critical analysis" -- "2.2. Macrocontextual analysis" -- "2.3. Synthesis" -- "3. The Complaint of Miriam and Aaron against Moses (Num 12)" -- "3.1. Literary-critical analysis" -- "3.2. Macrocontextual analysis" -- "3.3. Synthesis" -- "4. The Story of the Spies (Num 13â14)" -- "4.1. Literary-critical analysis of Num 13â14" -- "4.2. Macrocontextual analysis of Num 13â14
"4.3. Synthesis " -- "4.4. Literary-critical analysis of Deut 1:19-46" -- "4.5. Comparison of Num 13â14 and Deut 1:19-46" -- "4.6. Result" -- "5. Dathan, Abiram, the 250 Men, and Korah (Num 16â17)" -- "5.1. Literary-critical analysis" -- "5.2. Macrocontextual analysis" -- "5.3. Synthesis" -- "6. Result" -- "Chapter 7: From Kadesh to the Plains of Moab (Num 20â21 // Deut 1â3)" -- "1. Priestly Material in Num 20â21" -- "2. Israelâs Detour around Edom (Num 20:14-21)" -- "2.1. Literary-critical analysis" -- "2.2. Macrocontextual analysis" -- "2.3. Synthesis" -- "3. The Defeat of Sihon and Og (Num 21:21-35)" -- "3.1. Literary-critical analysis" -- "3.2. Macrocontextual analysis" -- "3.3. Synthesis" -- "4. The Mosaic Retrospective in Deut 1â3*" -- "4.1. Literary-critical analysis" -- "4.2. Macrocontextual analysis" -- "4.3. Synthesis" -- "5. Jephthahâs Speech in Judg 11:12-28" -- "6. The Relationship among the Parallel Accounts" -- "6.1. Comparison of individual motifs" -- "6.2. Synthesis" -- "7. The Itinerary Reports (Num 20:1, 22 -- 21:4a, 10-20 -- 22:1)" -- "7.1. Literary-critical analysis" -- "7.2. Macrocontextual analysis" -- "7.3. Synthesis" -- "8. Result" -- "Chapter 8: Balaam (Num 22â24)" -- "1. Literary-Critical Analysis" -- "2. Macrocontextual Analysis" -- "2.1. The first oracle (Num 23:7-10)" -- "2.2. The second oracle (Num 23:18b-24) " -- "2.3. The third oracle (Num 24:3-9)" -- "2.4. The fourth through seventh oracles (Num 24:15-24)" -- "2.5. The prose narrative" -- "3. Synthesis" -- "Chapter 9: Preparations for Conquest (Josh 1â5)" -- "1. Instructions prior to Entering the Land (Josh 1)" -- "1.1. Literary-critical analysis" -- "1.2. Macrocontextual analysis" -- "1.3. Synthesis" -- "2. Rahab and the Spies (Josh 2)" -- "2.1. Literary-critical analysis" -- "2.2. Macrocontextual analysis" -- "2.3. Synthesis
"3. The Crossing of the Jordan (Josh 3â4)" -- "3.1. Literary-critical analysis" -- "3.2. Macrocontextual analysis" -- "3.3. Synthesis" -- "4. A Bookend to the Exodus (Josh 5)" -- "4.1. Literary-critical analysis" -- "4.2. Macrocontextual analysis" -- "4.3. Synthesis" -- "5. Result" -- "Chapter 10: The Conquest of Jericho and Ai (Josh 6â8)" -- "1. The Conquest of Jericho (Josh 6)" -- "1.1. Literary-critical analysis" -- "1.2. Macrocontextual analysis" -- "1.3. Synthesis" -- "2. Achanâs Sin (Josh 7)" -- "2.1. Literary-critical analysis" -- "2.2. Macrocontextual analysis" -- "2.3. Synthesis" -- "3. The Conquest of Ai (Josh 8)" -- "3.1. Literary-critical analysis of Josh 8" -- "Excursus: The manuscript evidence for Josh 8:10-13" -- "3.2. Macrocontextual analysis of Josh 8" -- "3.3. Literary-critical analysis of Judg 20" -- "3.4. Comparison of Josh 8 and Judg 20 " -- "3.5. Synthesis" -- "4. Result" -- "Chapter 11: The Conquest of the Remainder of the Land (Josh 9â12)" -- "1. The Gibeonite Accord (Josh 9)" -- "1.1. Literary-critical analysis" -- "1.2. Macrocontextual analysis" -- "1.3. Synthesis" -- "2. The Conquest of the South (Josh 10)" -- "2.1. Literary-critical analysis" -- "2.2. Macrocontextual analysis" -- "2.3. Synthesis" -- "3. The Conquest of the North (Josh 11)" -- "3.1. Literary-critical analysis" -- "3.2. Macrocontextual analysis" -- "3.3. Synthesis" -- "4. The List of Conquered Cities (Josh 12)" -- "4.1. Literary-critical analysis" -- "4.2. Macrocontextual analysis" -- "4.3. Synthesis" -- "5. Result" -- "Chapter 12: Conclusion" -- "1. The Theoretical Problem and a Proposed Solution" -- "2. Synthesis and Evaluation of the Results" -- "2.1. The earliest exodus-conquest narrative" -- "2.2. Pre-priestly expansions to the exodus-conquest narrative" -- "3. Implications for the Formation of the Hexateuch" -- "Bibliography
"Index of Ancient Sources" -- "Index of Modern Authors" -- "Subject Index
Keywords: Bibel; Bibel; Bibel; Bibel; Bibel; Auszug aus Ägypten; Erzähltheorie; Exodustradition; Komposition; Exodus, The ; Biblical teaching; Electronic books; Sinai; Hochschulschrift